CO2 mineralization of bottom ash and decarbonation of waste-to-energy plants - Carine Julcour; Amar Dandach; Laurent Cassayre; Florent Bourgeois (Journal of CO2 Utilization)
Following the Paris agreements on climate change, CO2 emissions from large emitters have become the focus of particular attention. With a national average of 0.4 kg of fossil CO2 emitted per kg of Municipal Solid Waste (MSW) incinerated, bottom ash (BA) residues from waste-to-energy (WtE) plants in France are possible candidates for CO2 mitigation by mineralization, considering BA as feedstock for CO2 capture and production of alternative construction materials.BA samples collected from an operating WtE plant in the suburb of Lyon were carbonated under slurry or humidity-controlled conditions. It was found that 35 kg of CO2 could be captured per tonne of minus 100 μm ground BA in 30–120 min at ambient conditions. A water pre-washing stage was necessary to prevent the production of H2 by oxidation of Al metal during carbonation and removed chlorides and sulfates that are undesirable in construction materials.While it is argued that CO2 mineralization is of limited interest for mitigating the CO2 emissions of WtE facilities, a conservative analysis of a production system that associates a WtE plant and a cement plant reveals that the net carbon footprint of such a combined production system could be reduced by 15 % with an added mineralization process.